2019
DOI: 10.9734/jpri/2019/v29i430246
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Self-medication among Pharmacy Students in North Cyprus

Abstract: Aim: The aim of our study is to assess the attitude, knowledge and practice of self-medication among fifth year Pharmacy Students at Near East University in Northern Cyprus. Study Design: A cross sectional study. Place and Duration of Study: The study was conducted in faculty of pharmacy in Near East University in Northern Cyprus on 28 of December 2018. Methodology: A 7- part self administered questionnaire was used among fifth year pharmacy students who were available during the study time.&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(26 reference statements)
0
4
1
Order By: Relevance
“…This study includes three geographical areas (3 states of Pakistan include Punjab, Sindh and Azad Kashmir). The prevalence of self -medication of OTC and other prescription drugs in our study was found to be 88% which is less than those studies conducted in Saudi Arabia 98.7% [4] Lahore 95% [5], Yemen 93% [6], Eritrea 93.7% [7] and higher then that Germany 27.7% [8], India Rajpur Punjab 80% [9], Turkey 19.1% [10], Cyprus 30.7% [11], Malaysia 80.9% [12], Cameroon 73.8% [13], Nepal 48.2% [14], Iraq 84.8% [15], Peshawar 64.8% [16], Vietnam 83.3% [17]. The commonly used OTC and other prescription drugs are Paracetamol 77.5%, Multivitamin 38.9% and Omeprazole 36.4%.…”
Section: Discussioncontrasting
confidence: 78%
“…This study includes three geographical areas (3 states of Pakistan include Punjab, Sindh and Azad Kashmir). The prevalence of self -medication of OTC and other prescription drugs in our study was found to be 88% which is less than those studies conducted in Saudi Arabia 98.7% [4] Lahore 95% [5], Yemen 93% [6], Eritrea 93.7% [7] and higher then that Germany 27.7% [8], India Rajpur Punjab 80% [9], Turkey 19.1% [10], Cyprus 30.7% [11], Malaysia 80.9% [12], Cameroon 73.8% [13], Nepal 48.2% [14], Iraq 84.8% [15], Peshawar 64.8% [16], Vietnam 83.3% [17]. The commonly used OTC and other prescription drugs are Paracetamol 77.5%, Multivitamin 38.9% and Omeprazole 36.4%.…”
Section: Discussioncontrasting
confidence: 78%
“…Self-medication is a common and regular practice of using medicines, common over-the-counter (OTC) drugs without any medical supervision, by the people themselves for self-treatment, considering it a part of selfcare in both developed and developing countries [1,2]. Self-medication is reported to be higher in developing countries, mostly due to the fact that people generally consider it as first aid in treating minor ailments or acute symptoms such as vomiting, headache, nausea, fever, and cold [3].…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed that easily accessibility of medicines (44.7%) from private pharmacies without prescription could explain the high percentage of purchasing from these pharmacies as a major source of the practice of SM (WHO, 2000). Also, keeping medicines at home (80%) is an important concern led to increase the possibility of SM and mistakes in proper consumption (Khamis et al, 2019).…”
Section: Sources Of Medications and Information On Smmentioning
confidence: 99%